Effect of Intra Spacing on Yield and Yield Components of Carrot (Daucus Carrota L.Sub Sp. Sativus) - Shiberu, Tadele; Tamiru, Selomon (Current Research in Agricultural Sciences, 2016)
The experiment was conducted in 2014 cropping seasons to study the effect of intra row spacing on yield and yield components of carrot. The crop was grown in July to October (105 days) with five treatments (5, 7.5, 10, 12.5 and 15 cm) in randomized complete block design with three replications. Root length, leaf fresh weight, root fresh weight, and root diameter weight were significantly different among treatments. The maximum root length (20.3 cm), root diameter (59.67 mm), root fresh weight (182. 33g plant-1) and fresh leave weight (129.67 g plant-1) were found in 15 cm spacing, whereas the highest total root yield per hectare was found in treatment 5 and 7.5cm; 55.15, and 54.75 ton, respectively.